Life Insurance Services and their Development in Lithuania - Kindurys, Vytautas (Ekonomika, 2002)
In this article there is a study of life insurance services business as an independent insurance branch. reasons and circumstances of it’s origin. Author formulates the main life insurance services. There is analysis of other authors’ presented life insurance conception (essence) versions. The original life insurance service definition is presented in this article. The author shows what role life insurance services development plays from the individual and society point of view. A lott attention is paid to life insurance services classification. Different authors attitudes are show on this question. Lithuanian life insurance services grouping in organization practice is presented here. In author’s opinion, when classifying life insurance services it is purposive to base on these criteria: insurance object, insurance subject, insurance premium payment procedure. validation of insurance contract, form of insurance protection, method of insurance contract conclusion. In Lithuania life insurance services business as independent branch of insurance business started to form 1997. At the moment Lithuanian life insurance companies offer for clients life insurance services products similar to Western countries life insurance companies services products. In Lithuania there are seven life insurance companies with foreign capital out of nine active. Lithuanian life insurance services market development tendencies are similar to this kind of markets primary development stages tendencies in Western countries. Life insurance services development practice confirm theoretical propositions formulated in an article about life insurance services necessity, essence and role.